The Effect of Implementation of Human Resource System on The Business Environment: A Review of the Articles - Edi Putra; Aprilian Rufianto; Try Junanto; Ai Suminar (OIKONOMIA: Journal of Economics and Management Science, 2023)
This study is a form of study related to human resource relations research in the field of entrepreneurship industry where the entrepreneurial aspect is currently in the public spotlight. More precisely, the entrepreneurial industry at this time is better at using the human resource aspect to be used as a competency test material. Thus,people at this time use more human resources as the main help in the field of entrepreneurship. The main purpose of this study is to determine the form of influence exerted from the implementation of human resource studies in the current entrepreneurial environment. The method used in this study is a form of literature study method by applying elements of qualitative methods from various journals. The results of the study show some of the influences that occur due to the use of human resources which refer to several results, namely; (1) The practices and roles brought by human resources absorb more energy and provide significant results in the business world; (2) the progress of the business world is greater with the significance aspect of human resources which is very closely related compared to other types of sources. This is because the external and internal factors of human resources provide aspects that are not the least especially in the development or preparation of business materials; (3) the maximization of productivity or performance that is present especially in the business field which certainly affects consumers or the image of a business industry in the world of marketing. These three results gain a very large share of significance in the field of the entrepreneurial industry sector and are also supported by the results of study studies obtained from several journals related to the influence of human resources in an entrepreneurial industry.